2010
DOI: 10.1073/pnas.1001229107
|View full text |Cite
|
Sign up to set email alerts
|

Similar patterns of cortical expansion during human development and evolution

Abstract: The cerebral cortex of the human infant at term is complexly folded in a similar fashion to adult cortex but has only one third the total surface area. By comparing 12 healthy infants born at term with 12 healthy young adults, we demonstrate that postnatal cortical expansion is strikingly nonuniform: regions of lateral temporal, parietal, and frontal cortex expand nearly twice as much as other regions in the insular and medial occipital cortex. This differential postnatal expansion may reflect regional differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
589
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 658 publications
(681 citation statements)
references
References 59 publications
(70 reference statements)
53
589
2
3
Order By: Relevance
“…Those sulcal dimensions still show substantially lower heritability in humans than do the developmentally and evolutionarily primary sulci such as the central sulcus and the Sylvian fissure. Studies of cortical development in humans have shown differential regional enlargement, which has been suggested to reflect extended maturation and complexity of dendritic and synaptic architecture in association areas (24). Lateral temporal, lateral parietal, and dorsal and medial prefrontal regions show the greatest degree of expansion from birth to adulthood, and it has been suggested that cortical circuits in these regions may be more sensitive to postnatal experience (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those sulcal dimensions still show substantially lower heritability in humans than do the developmentally and evolutionarily primary sulci such as the central sulcus and the Sylvian fissure. Studies of cortical development in humans have shown differential regional enlargement, which has been suggested to reflect extended maturation and complexity of dendritic and synaptic architecture in association areas (24). Lateral temporal, lateral parietal, and dorsal and medial prefrontal regions show the greatest degree of expansion from birth to adulthood, and it has been suggested that cortical circuits in these regions may be more sensitive to postnatal experience (24).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of cortical development in humans have shown differential regional enlargement, which has been suggested to reflect extended maturation and complexity of dendritic and synaptic architecture in association areas (24). Lateral temporal, lateral parietal, and dorsal and medial prefrontal regions show the greatest degree of expansion from birth to adulthood, and it has been suggested that cortical circuits in these regions may be more sensitive to postnatal experience (24). Heritability patterns observed in chimpanzees and humans in the present study are consistent with the proposition that humans have evolved relaxed genetic control on cortical organization, especially in areas related to higher-order cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, transmodal regions of the DMN, although located at distant points of the rostrocaudal axis, have similar gene expression patterns. These regions also show protracted developmental expansion and maturation in humans [63]. While much remains to be learned about neurodevelopmental gradients in the human cerebral cortex, such research can help to integrate observations across different cortical features and establish an informed developmental basis for the proposed intrinsic coordinate system.…”
Section: Glossarymentioning
confidence: 98%
“…This approach provides evidence of hotspots of human evolution in lateral temporal, parietal, and prefrontal cortex that have expanded dramatically in the human lineage relative to that in the macaque; the pattern is remarkably similar to human postnatal cortical expansion, between birth and adulthood (Van Essen and Dierker 2007;Hill et al 2010). To better understand this pattern of evolutionary divergence, it is desirable to have a larger set of known or presumed homologies between specie, and also to have improved methods of interspecies registration that handle the highly nonuniform spatial patterns of expansion.…”
Section: Interspecies Registrationmentioning
confidence: 98%
“…2 Group-average myelin maps for macaque (n ¼ 19, Yerkes19) and human (n ¼ 196, HCP), adapted from Glasser et al (2013a. Myelin maps were generated by computing the T1w/T2w ratio for each cortical gray matter voxel, mapping it to individual cortical surfaces, and registering the individuals to a species-specific atlas surface (Glasser and Van Essen 2011) using the MSM registration method myelinated higher cognitive regions, whereas the least expansion (~2-fold) occurs in early sensory areas (Hill et al 2010). A likely cellular-level correlate is that, in the macaque, dendritic arbors sizes and synapse number increase between birth and adulthood in inferotemporal cortex, whereas there is a net decrease in both measures for early visual areas (Elston et al 2010).…”
Section: Convolutions and Folding Variabilitymentioning
confidence: 99%